The Effectiveness of Women's Leadership in Implementing Development in Negeri Haria Central Maluku - Tuhumury, Sofpia; Sahetapy, Petronela; Patty, Julia Th. (Jurnal Studi Ilmu Pemerintahan, 2023)
This research aims to explain the effectiveness of women's leadership in the implementation of development in the Negeri Haria. This study is a study that uses qualitative methods aims to find out the leadership style and inhibiting factors for female leaders in the implementation of development. This research was conducted in the Negeri Haria Central Maluku Regency. Primary data collection is carried out through interviews with a number of informants who are considered directly involved in the process of effectiveness of women's leadership in the implementation of development in the Negeri Haria. The results of this study describe that the leadership style of women used has been going well but not yet effective, this is caused by a lack of public trust in women's leadership so that it becomes an obstacle in the process of implementing development. The results of this research are expected to become reference material for the science of government and public services from the perspective of women's leadership in local government in Indonesia.